PERAN PEMERINTAH DALAM RELOKASI PEDAGANG KAKI DI KAWASAN PARIWISATA MALIOBORO - Mahnunah, Ni'mah; Mafatih, Ahmad Fakhrul (Jurnal Perencanaan dan Pengembangan Kebijakan, 2024)
The Malioboro area is a very well-known tourist destination in the Special Region of Yogyakarta and is also the most favorite place to visit for local and foreign tourists, especially those closest to visit, namely the street vendors in the Malioboro area, but in early 2022 there was a move or relocation Street vendors who were originally on the pedestrian route have now moved to Malioboro Terrace, to organize the Malioboro area and to realize the ideals of the philosophical axis area as a world cultural heritage. Through qualitative descriptive research, we want to answer the government's role in relocating street vendors in the Malioboro tourism area. The results of the research obtained are that the role played by local governments can be identified which includes planning, implementation, as well as monitoring and evaluation.